The landslide traces inventory in the transition zone between the Qinghai-Tibet Plateau and the Loess Plateau: a case study of Jianzha County, China - Li, Tao; Xu, Chong; Li, Lei; Xu, Jixiang (Frontiers in Earth Science, 2024)
The upper reaches of the Yellow River in China, influenced by erosion of the Yellow River and tectonic activities, are prone to landslides. Therefore, it is necessary to thoroughly investigate the existing landslide traces. Considering that the existing records of landslide traces in Jianzha County, China are not sufficiently complete and detailed, a currently most objective and complete landslide traces inventory has been compiled for the county. This was primarily achieved through visual interpretation based on various high-resolution satellite images and terrain data, supplemented and validated by existing landslide records. The results indicate that within the study area of 1714 km 2 , the area affected by landslides accounts for 7.37%. The landslide inventory contains a total of 713 landslides, ranging in scale from 3556 m 2 to 11.13 km 2 , with a total area of 134.46 km 2 . These landslides are primarily distributed in the relatively low-elevation northeastern part of Jianzha County, characterized mainly by large-scale loess landslides, with 14 landslides exceeding 10 6 m 2 . Through quantitative analysis, the maximum point density and area density of landslides are 3.94 km - 2 and 1.12%, respectively. This inventory not only supplements the landslide trace data in the transition zone between the Qinghai-Tibet Plateau and the Loess Plateau, but also provides an important basis for subsequent landslide risk zoning, response to climate change, and landscape evolution. Additionally, it holds significant reference value for compiling landslide inventories in similar geological environments.